If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -13 + -1x + -9 + -10x = 0 Reorder the terms: -13 + -9 + 12x + -1x + -10x = 0 Combine like terms: -13 + -9 = -22 -22 + 12x + -1x + -10x = 0 Combine like terms: 12x + -1x = 11x -22 + 11x + -10x = 0 Combine like terms: 11x + -10x = 1x -22 + 1x = 0 Solving -22 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 1x = 0 + 22 Combine like terms: -22 + 22 = 0 0 + 1x = 0 + 22 1x = 0 + 22 Combine like terms: 0 + 22 = 22 1x = 22 Divide each side by '1'. x = 22 Simplifying x = 22
| Y=28.5x | | 5x-15+6=5-10 | | 96a/75xy | | 3x-6+1=-2-4x-(x-1) | | 180-x=10+180-3x | | 5=x(x-4) | | -3x-(x+4)=-4(x-1) | | 125=60p+5 | | 4x-6n=-46 | | 55.25n=.85 | | x(x-7)+14=2x | | 7x+1+10x+9=180 | | -24=-8n+4n | | 4x+3y=365 | | 7x+1+10x+9+38=180 | | 2(x+7)=12-4x+10 | | 5w-7=27 | | 3x+4x=365 | | 2(x+5.5)+2(4.5)=48 | | 3y^3-2y^2-y=0 | | -3+1+n=9 | | -7=5x-6 | | 28=-67x-12+2x | | M-(-8)=-4 | | 9u-39=-4u | | 17+18+5f=-13+11f | | 20x=-9x | | -8u-20=-16u+4 | | x(4x+5)=-1 | | -1=3v+5 | | -7x=24x | | -7-20=-46 |